Propaganda and Communications in World History - Lerner, Daniel; Lasswell, Harold D.; Weitzman, Michael; Bermant, Chaim (1979)
50-110 J. J. Finkelstein, Early Mesopotamia, 2500-1000 B.C.; 111-144 A. L. Oppenheim, Neo-Assyrian and Neo-Вabylonian Empires (Society and political organization; royal propaganda).